RANCANGAN E-LOGBOOK BERBASIS WEB DAN DATABASE UNTUK TEKNISI TELEKOMUNIKASI DAN NAVIGASI UDARA - Mohammad Berlian Lindu Agung; Nyaris Pambudiyatno; Romma Diana Puspita (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Currently PERUM LPPNPI Yogyakarta use paper-based logbooks in recording and managing maintenance data. There are 2 types of logbooks, logbook technicians and logbook equipment. The equipment-specific logbook is still divided into a number of equipment owned. Every day for the purposes of recording and processing maintenance data, at least a technician must fill out and process more than 10 logbook. This is very inefficient and tends to be wasteful, especially waste paper because each logbook is only valid for 1 month. This web-based and database E-Logbook was created using 4 collaborative applications Visual Studio Code, XAMPP, Apache and MySql. This E-Logbook application has 2 main features, namely a technician logbook and an equipment logbook. In addition, in this e-logbook there is equipment data that displays all equipment along with their specifications and conditions. Then there are additional features that are useful for giving announcements and assigning tasks to individual technicians. The E-Logbook work system is supported by hosting with 30GB of storage memory and 1Mbps bandwidth. With these specifications and existing designs, the result of the E-Logbook can replace the conventional Logbook function. Not only replacing it, E-Logbook can increase efficiency because it is paperless, has high security, is easy to use because it can be accessed anywhere and anytime through any device such as Smartphones and PCs.